(untitled) (Bangladesh Journal of Anatomy, 2020)
Background: Dimensional relationship among various body parts and stature has been the focus of anatomists, forensic medicine specialists, anthropologists and orthopedicians.Standard radiographic measurements can provide accuracy in measurement of bony dimensions. Thus, the present study was performed to calculate hand length and hand breadth from digital radiographs of hand and wrist joints and to find out their correlation with stature. Objectives: The objective of the study was to determine hand length and hand breadth from digital radiograph of hand and wrist joint (P/A view), to evaluate stature and also to find out the correlation of hand length and hand breadth with stature. Materials and Methods: Digital radiographs of hand and wrist joint (P/A view) were taken from 50 male students of Sir Salimullah Medical College, Dhaka within the age of 20-25 years of age. Stature of study subjects were measured by stadiometer. Then the radiographs were imaged and transferred to computer according to scale. Finally, hand length and hand breadth were measured by using MB ruler software. Correlation betweenhand length and hand breadth with stature was observed by using Pearson’s Correlation Coefficient test. Results: The mean ± SD of stature was 169.72 ± 5.06 cm.The mean ± SDof hand length was 19.08 ± 0.75 cm (range 17.7 - 21.3 cm) and the mean ± SD of hand breadth was 6.89 ± 0.40 cm. Hand length ( r = .414) and hand breadth ( r = .563) both had significant positive correlation with stature ( p<0.001). Conclusion: Stature has significant positive correlation with hand length and hand breadth was concluded. Bangladesh Journal of Anatomy January 2020, Vol. 18, No. 1, pp. 7-11